High-water-absorption sodium polyacrylate-based two-component polyurethane material and preparation method thereof
A sodium polyacrylate-based polyurethane material addresses moisture retention and structural weaknesses in polyurethane grouting by embedding sodium polyacrylate powder, improving water absorption and durability while maintaining fast curing and adhesion.
Patent Information
- Application Number
- CN202411317814.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2024-12-27
AI Technical Summary
Existing polyurethane grouting materials used in underground projects suffer from poor water absorption, leading to moisture retention, erosion, and structural weaknesses, with rapid heat release causing yellowing and burning, and inadequate compressive strength.
A highly water-absorbent sodium polyacrylate-based two-component polyurethane material is developed by embedding sodium polyacrylate powder in polyurethane open-cell foam, enhancing water absorption, bonding strength, and durability while maintaining fast curing and adhesion properties.
The material effectively absorbs moisture, prevents structural degradation, enhances bonding strength, and improves durability by avoiding material yellowing and burning, while maintaining high compressive strength and fast curing.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polymer material synthesis, and in particular to a highly water-absorbent sodium polyacrylate-based two-component polyurethane material and a preparation method thereof. Background Art
[0002] my country's underground projects are huge in scale. After years of service, the number of underground project diseases has gradually increased. Among them, leakage is one of the prominent problems that affect its service effect, especially in underground projects such as tunnels, basements, and urban underground pipelines. The leakage problem is more serious. At present, the most commonly used method to treat underground structure leakage is grouting. The grouting part can be repaired by using the adhesion, solidification, and filling effects of the slurry on the leakage channel. Among the many grouting materials, polyurethane grouting materials have been widely used in grouting plugging due to their good expansion, high early strength, strong adhesion, fast curing speed, good durability, and simple grouting operation.
[0003] In actual applications, after grouting is completed, some moisture will still remain in the cracks of tunnels, urban underground projects, etc. and cannot be discharged. The presence of this moisture will cause erosion to the building materials again, resulting in cracks, mildew spots, steel corrosion and other problems in the structure. Polyurethane materials have poor water absorption properties and cannot solve the above problems in actual applications. In addition, the reaction of isocyanate, water and polyol components in polyurethane materials will release a large amount of heat. The polymer material formed by solidification has a large density and solidifies quickly. The solidification time is ≤10s. At the same time, in order to achieve the repair effect, more raw materials may be grouting. The superposition of these four factors makes the internal temperature of the material higher, which is easy to cause yellowing and burning of the foam. The compressive strength of the foam after yellowing and burning is much less than 0.8Mpa, which weakens the repair effect of the polyurethane grouting material to a certain extent.
[0004] Therefore, in this field, there is an urgent need to develop a grouting plugging material with ideal strength, good durability and strong water absorption to meet the needs of plugging and reinforcing tunnels and underground projects. Summary of the invention
[0005] To solve the above technical problems, the present invention provides a highly water-absorbent sodium polyacrylate-based two-component polyurethane material and a preparation method thereof, by wrapping a highly water-absorbent sodium polyacrylate component in a polyurethane material, and constructing by grouting, the construction process is simple and convenient, and the material can be quickly infiltrated into the depths of the cracks, with the advantages of being fast, environmentally friendly, durable, slightly damaged, having strong water absorption, and good adhesion. The present invention uniformly embeds highly water-absorbent sodium polyacrylate powder in polyurethane open-cell foam, which not only retains the advantages of good expansibility, high early strength, strong adhesion, fast curing speed, good durability, and simple grouting operation of polyurethane materials, but also gives the material extremely high water absorption performance, effectively avoids the problems of material core burning, and can effectively enhance the bonding strength of the material, the structural strength of the foam body, the flame retardant and other properties, and prevents the foam from shrinking. At the same time, the presence of highly water-absorbent components in the material can quickly absorb the moisture at the leakage disease, enhance the bonding strength of the polyurethane material and the disease, and further improve the repair effect.
[0006] The highly water-absorbent sodium polyacrylate-based two-component polyurethane material and the preparation method thereof provided by the present invention include two components A and B, wherein component A includes:
[0007] 10-20 parts of sodium polyacrylate;
[0008] 80-100 parts of modified isocyanate component;
[0009] Component B includes:
[0010] 80-100 parts of polyol component;
[0011] 5-20 parts of physical foaming agent;
[0012] The surfactant accounts for 2-3% of component B;
[0013] The pore opening agent accounts for 2-3% of component B.
[0014] Preferably, the modified isocyanate in component A is obtained by prepolymerizing 10-40 parts of at least one hydrophilic polyol with 50-90 parts of isocyanate, wherein the hydrophilic polyol is at least one of polyethylene glycol 200, polyethylene glycol 400, and diethylene glycol, and the isocyanate is at least one of polymethylene polyphenyl isocyanate, modified diphenylmethane diisocyanate, and modified toluene diisocyanate.
[0015] Preferably, the sodium polyacrylate is in powder form with a density of 1.32 g / cm3.
[0016] Preferably, the polyols in the polyol component in component B are polyether polyols and polyester polyols, wherein the polyether polyol is at least one of sucrose polyether polyol and sorbitol polyether polyol, and has a hydroxyl value of 150 to 700 mgKOH / g, and the polyester polyol is a polyester polyol generated by a condensation reaction of phthalic anhydride or phthalic acid and diethylene glycol, ethylene glycol or butanediol.
[0017] Preferably, the physical foaming agent in component B is at least one of n-butane (boiling point -0.5°C), isobutane (boiling point -11.8°C), heptafluoropropane (boiling point -16.4°C), 1,-1-difluoroethane (boiling point -24.7°C), and dimethyl ether (boiling point -24.9°C), accounting for 5 to 20% of the total weight of the polyol component.
[0018] Preferably, the surfactant in component B is a non-silicone surfactant.
[0019] Preferably, the pore opening agent in the component B is at least one of polyoxypropylene-oxyethylene copolyether and polyoxyalkylene-polysiloxane copolymer.
[0020] The present invention also provides a preparation and application of a highly water-absorbent sodium polyacrylate-based two-component polyurethane material, which is applied to the preparation and application of the highly water-absorbent sodium polyacrylate-based two-component polyurethane material, and comprises the steps of:
[0021] Step 1: Heat the reactor to 40-50°C, add polyol and isocyanate in sequence, and then heat the reactor to 78-82°C for 1.5-2.5h;
[0022] Step 2: After cooling the modified isocyanate obtained in step 1, add sodium polyacrylate powder, stir for 20 minutes to mix evenly, so that the sodium polyacrylate powder is evenly dispersed in the isocyanate to form a liquid component A;
[0023] Step 3: preparing an open-cell polyurethane foam polyol to form a liquid component B;
[0024] Step 4: Detect the leakage site, arrange grouting holes according to the on-site detection results, mix component A and component B in a grouting machine, and use the reaction of isocyanate groups (-NCO) and hydroxyl groups (-OH) to embed highly absorbent sodium polyacrylate resin into the open-cell polyurethane foam to synthesize a grouting material with strong water absorption. The highly absorbent resin is then delivered to the service location using a grouting transportation method, which is convenient and quick.
[0025] Preferably, the stirring temperature in step 2 is room temperature, and the stirring time is not less than 20 min.
[0026] Compared with the related art, the highly water-absorbent sodium polyacrylate-based two-component polyurethane material and the preparation method thereof provided by the present invention have the following beneficial effects:
[0027] 1. The present invention uniformly embeds highly water-absorbent sodium polyacrylate powder into polyurethane open-cell foam. The generated grouting material is a solid honeycomb structure with ultra-long and ultra-strong water absorption and dehydration effects. It can quickly absorb moisture at the leakage site, enhance the strength of the polyurethane foam, keep the leakage site dry, enhance the bonding strength of the interface between the polyurethane material and the site, avoid the re-erosion of building materials by moisture, avoid the re-occurrence of cracks, mildew spots, steel corrosion and other problems, and further improve the repair and treatment effect of water leakage in underground engineering structures.
[0028] 2. Giving the material extremely strong water absorption can prevent excessive reaction between polyurethane material and water, causing the material volume to expand excessively and resulting in low compressive strength of the foam.
[0029] 3. Improving the water absorption of polyurethane grouting materials is beneficial for it to absorb moisture from leakage defects, which helps to enhance the bonding strength between polyurethane materials and defective parts, and can further improve the repair effect.
[0030] 4. Polyurethane materials will react and release a large amount of heat during the curing process, giving the material strong water absorption, which can effectively reduce the formation of pores and channels caused by structural deformation and temperature difference, and can effectively avoid the problem of yellowing and burning core inside the foam, thereby enhancing the durability of the material and reducing the possibility of leakage.
[0031] 5. Sodium polyacrylate can absorb dozens to thousands of times its own water. Embedding highly water-absorbent sodium polyacrylate in polyurethane foam can effectively improve the overall flame retardant properties of the material.
[0032] 6. The urban ground environment is complex and often does not have the conditions for excavation and maintenance. Polyurethane grouting repair does not require excavation, and the construction process is convenient and fast. Polyurethane materials have good expansion properties, which can not only quickly block pipeline leakage, but also effectively solve the foundation degassing and loosening problems caused by leakage in tunnels, basements, and underground pipeline projects.
[0033] 7. During grouting, the isocyanate component and the polyol component react rapidly to form a high-strength polymer skeleton in a short period of time. The highly absorbent resin is evenly embedded in the high-strength polymer skeleton, which effectively makes up for the lack of strength and poor durability of general highly absorbent resins. While ensuring the water absorption and dehydration effect, it can also provide support for the repair site and improve the stability of the repair structure. DETAILED DESCRIPTION
[0034] The specific implementation of the present invention is given below to further illustrate the present invention. Obviously, the examples described below are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] Embodiment 1:
[0036] Table 1-1 Composition of component A
[0037]
[0038] Table 1-2 Composition of component B
[0039]
[0040] Production steps:
[0041] Step 1: Heat the reactor to 50°C, add polymethylene polyphenyl isocyanate, polyethylene glycol 200, and polyethylene glycol 400 in sequence according to the proportions in Table 1-1, then heat the reactor to 80°C and react for 2h.
[0042] Step 2: After cooling the modified isocyanate obtained in step 1, add sodium polyacrylate powder, stir for 20 minutes to mix evenly, so that the sodium polyacrylate powder is evenly dispersed in the isocyanate to form a liquid component A;
[0043] Step 3: Prepare component B, add polyol component, physical foaming agent, surfactant, and cell opener in the proportions in Table 1-2, and stir for 20 minutes to mix evenly;
[0044] Step 4: Use a high-pressure grouting machine to mix components A and B. After the slurry solidifies, the mechanical properties and water absorption properties of the material are tested. The various physical properties are shown in Table 1-3:
[0045] Table 1-3 Various physical properties
[0046] Physical properties unit Test Results Test Standards Solidification time s 10 Visual inspection Appearance - Uniform light yellow solid Visual inspection density <![CDATA[Kg / m 3 ]]> 235 GB / T6343-2009 Compressive strength MPa 1.43 GB / T8813-2009 Water absorption g / g 676.3 GB / T1034-2008
[0047] Embodiment 2:
[0048] Table 2-1 Composition of component A
[0049]
[0050] Table 2-2 Composition of component B
[0051]
[0052] Production steps:
[0053] Step 1: Heat the reactor to 50°C, add diphenylmethane diisocyanate, polyethylene glycol 200, and polyethylene glycol 400 in sequence according to the proportions in Table 2-1, then heat the reactor to 80°C and react for 2 hours.
[0054] Step 2: After cooling the modified isocyanate obtained in step 1, add sodium polyacrylate powder, stir for 20 minutes to mix evenly, so that the sodium polyacrylate powder is evenly dispersed in the isocyanate to form a liquid component A;
[0055] Step 3: Prepare component B, add polyol component, physical foaming agent, surfactant and cell opening agent in the proportions in Table 2-2, and stir for 20 minutes to mix evenly;
[0056] Step 4: Use a high-pressure grouting machine to mix components A and B. After the slurry solidifies, the mechanical properties and water absorption properties of the material are tested. The various physical properties are shown in Table 2-3:
[0057] Table 2-3 Various physical properties
[0058]
[0059]
[0060] Embodiment 3:
[0061] Table 3-1 Composition of component A
[0062]
[0063] Table 3-2 Composition of component B
[0064]
[0065] Production steps:
[0066] Step 1: Heat the reactor to 50°C, add diphenylmethane diisocyanate, polyethylene glycol 200, and polyethylene glycol 400 in sequence according to the proportions in Table 3-1, then heat the reactor to 80°C and react for 2 hours.
[0067] Step 2: After cooling the modified isocyanate obtained in step 1, add sodium polyacrylate powder, stir for 20 minutes to mix evenly, so that the sodium polyacrylate powder is evenly dispersed in the isocyanate to form a liquid component A;
[0068] Step 3: Prepare component B, add polyol component, physical foaming agent, surfactant and cell opening agent in the proportions in Table 3-2, and stir for 20 minutes to mix evenly;
[0069] Step 4: Use a high-pressure grouting machine to mix components A and B. After the slurry solidifies, the mechanical properties and water absorption properties of the material are tested. The various physical properties are shown in Table 3-3:
[0070] Table 3-3 Various physical properties
[0071] Physical properties unit Test Results Test Standards Solidification time s 10 Visual inspection Appearance - Uniform light yellow solid Visual inspection density <![CDATA[Kg / m 3 ]]> 246 GB / T6343-2009 Compressive strength MPa 1.43 GB / T8813-2009 Water absorption g / g 525.5 GB / T1034-2008
[0072] Embodiment 4:
[0073] Table 4-1 Composition of component A
[0074]
[0075] Table 4-2 Composition of component B
[0076]
[0077] Production steps:
[0078] Step 1: Heat the reactor to 50°C, add diphenylmethane diisocyanate, polyethylene glycol 200, and polyethylene glycol 400 in sequence according to the proportions in Table 4-1, then heat the reactor to 80°C and react for 2 hours.
[0079] Step 2: After cooling the modified isocyanate obtained in step 1, add sodium polyacrylate powder, stir for 20 minutes to mix evenly, so that the sodium polyacrylate powder is evenly dispersed in the isocyanate to form a liquid component A;
[0080] Step 3: Prepare component B, add polyol component, physical foaming agent, surfactant and cell opening agent in the proportions in Table 4-2, and stir for 20 minutes to mix evenly;
[0081] Step 4: Use a high-pressure grouting machine to mix components A and B. After the slurry solidifies, the mechanical properties and water absorption properties of the material are tested. The various physical properties are shown in Table 4-3:
[0082] Table 4-3 Various physical properties
[0083]
[0084]
[0085] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A highly water-absorbent sodium polyacrylate-based two-component polyurethane material, characterized in that: It includes two components, A and B, wherein component A includes: 10-20 parts of sodium polyacrylate; 80-100 parts of modified isocyanate component; Component B includes: 80-100 parts of polyol component; 5-20 parts of physical foaming agent; The surfactant accounts for 2-3% of component B; The pore opening agent accounts for 2-3% of component B.
2. The highly water-absorbent sodium polyacrylate-based two-component polyurethane material according to claim 1, characterized in that: The modified isocyanate in component A is obtained by prepolymerizing 10-40 parts of at least one hydrophilic polyol with 50-90 parts of isocyanate, wherein the hydrophilic polyol is at least one of polyethylene glycol 200, polyethylene glycol 400, and diethylene glycol, and the isocyanate is at least one of polymethylene polyphenyl isocyanate, modified diphenylmethane diisocyanate, and modified toluene diisocyanate.
3. The highly water-absorbent sodium polyacrylate-based two-component polyurethane material according to claim 1, characterized in that: The sodium polyacrylate is in powder form with a density of 1.32 g / cm 3 .
4. The highly water-absorbent sodium polyacrylate-based two-component polyurethane material according to claim 1, characterized in that: The polyols in the polyol component in component B are polyether polyols and polyester polyols, wherein the polyether polyol is at least one of sucrose polyether polyol and sorbitol polyether polyol, and the hydroxyl value is 150-700 mgKOH / g, and the polyester polyol is a polyester polyol produced by a condensation reaction of phthalic anhydride or phthalic acid and diethylene glycol, ethylene glycol or butanediol.
5. The highly water-absorbent sodium polyacrylate-based two-component polyurethane material according to claim 1, characterized in that: The physical foaming agent in the component B is at least one of n-butane, isobutane, heptafluoropropane, 1,-1-difluoroethane and dimethyl ether, accounting for 5-20% of the total weight of the polyol component.
6. The highly water-absorbent sodium polyacrylate-based two-component polyurethane material according to claim 1, characterized in that: The surfactant in component B is a non-silicone surfactant.
7. The highly water-absorbent sodium polyacrylate-based two-component polyurethane material according to claim 1, characterized in that: The pore opening agent in the component B is at least one of polyoxypropylene-oxyethylene copolyether and polyoxyalkylene-polysiloxane copolymer.
8. A method for preparing a highly water-absorbent sodium polyacrylate-based two-component polyurethane material, characterized in that: The method is applied to the preparation of the highly water-absorbent sodium polyacrylate-based two-component polyurethane material described in claims 1 to 7, and the method comprises the steps of: Step 1: Heat the reactor to 40-50°C, add polyol and isocyanate in sequence, and then heat the reactor to 78-82°C for 1.5-2.5h; Step 2: After cooling the modified isocyanate obtained in step 1, add sodium polyacrylate powder, stir for 20 minutes to mix evenly, so that the sodium polyacrylate powder is evenly dispersed in the isocyanate to form a liquid component A; Step 3: Prepare open-cell polyurethane foam polyol to form liquid component B.
9. The highly water-absorbent sodium polyacrylate-based two-component polyurethane material and the preparation method thereof according to claim 1, characterized in that: The stirring temperature in the step 2 is room temperature, and the stirring time is not less than 20 min.
10. The application of the highly water-absorbent sodium polyacrylate-based two-component polyurethane material prepared by the method according to claims 8-9 is divided into the following steps: The leakage site is inspected, and grouting holes are arranged according to the on-site inspection results. Component A and component B are mixed in a grouting machine. The sodium polyacrylate resin with high water absorption is embedded into the open-cell polyurethane foam by utilizing the reaction between isocyanate groups (-NCO) and hydroxyl groups (-OH) to synthesize a grouting material with strong water absorption. The highly absorbent resin is then delivered to the service location using a grouting transportation method, which is convenient and quick.
Citation Information
Patent Citations
Gel ice pad polyurethane stock solution, preparation method thereof and gel ice pad
CN115819715A
Hydrophilic polyurethane foam material
CN116903827A
Highly absorbent polyurethane foam
US4985467A